Efficacy and safety of thoracic radiotherapy combined with anti-angiogenic therapy and immunochemotherapy for advanced non-small cell lung cancer patients: a retrospective study - Gai, Kai; Shi, Xuexin; Xu, Fei; Ding, Xia; Liu, Lu; Zhang, Longjie; Wang, Hao; Chen, Ling (Frontiers in Oncology, 2025)
PurposeTo assess the efficacy and safety of radiotherapy combined with anti-angiogenic therapy, immune checkpoint inhibitors, and chemotherapy for advanced non-small cell lung cancer (NSCLC).MethodsPatients who have received at least two cycles of quadruple therapy were Progression-free survival (PFS), overall survival (OS), and treatment-related side effects were comprehensively evaluated using R language and the chi-square test.ResultsSeventy-four patients were enrolled and divided into two groups (A and B) based on whether they had received radiotherapy. The incidence rate of adverse events—such as radiation-related pneumonitis, pneumonia, thrombocytopenia, cough, panting, fatigue, and radiodermatitis—were significantly higher in patients receiving radiotherapy. A survival analysis comparing the experimental and control groups revealed that the addition of radiotherapy played a positive role in extending PFS and OS, with statistically significant results observed for OS (HR(95%CI)=0.51[0.283, 0.919]; p =0.019). The risk of radiation-related pneumonitis was significantly higher than in the control group (p <0.001) and was associated with a negative impact on prognosis; a similar trend was also observed for pneumonia (p=0.041) and thrombocytopenia (p <0.001).ConclusionsSequential radiotherapy after quadruple therapy can prolong survival in patients with advanced NSCLC. However, special attention should be paid to treatment-related side effects such as pneumonitis, pneumonia, and thrombocytopenia, which may negatively affect prognosis.